THE EFFECT OF THE POMODORO TECHNIQUE ON STUDENTS’ WRITING PERFORMANCE ACROSS CRITICAL THINKING LEVELS - Yohana, Elva; Fitriana, Anjali; Kristanti, Maharani (Jurnal Bahasa Lingua Scientia, 2025)
Pomodoro technique deals with the time management of the students in writing descriptive text. Furthermore, this paper reports on investigating the effect of the Pomodoro technique combined with video learning on students’ performance across critical thinking levels. The study was implemented by employing forty-five students of the English Language department in Indonesia. The experimental group and the control group were used to assign them to assess students’ writing performance across critical thinking levels. Therefore, the pre-test and post-test in writing conducted in this study to get the quantitative data analysis whereas the questionnaire was given after the post-test was used to get the qualitative data on students' critical thinking levels. The result of this study revealed that the Pomodoro technique combined with video learning was effective to enhance the students' writing performance. Additionally, the different levels of students' critical thinking in the experimental group would not affect the students' writing performance even there was the treatment taught in it.